Ownership Structure and Corporate Governance Effects on Green Banking Disclosure - Salsahbilah Salsahbilah; Siti Jubedah (Jurnal Akuntansi, 2026)
Purpose – This study aims to examine the influence of foreign ownership, board size, independent commissioner, and audit committees on green banking disclosure. Design/Methodology/Approach – A causal research utilizing a quantitative method and existing data. The target group includes banking firms listed on the Indonesia Stock Exchange from 2022 through 2024. The sample design employs judgmental sampling, where samples are chosen based on various criteria for financial institutions on the Indonesia Stock Exchange that regularly publish annual and sustainability reports. Findings – The findings reveal that foreign ownership significantly and negatively impacts green banking disclosure, while the size of the board of commissioners significantly and positively influences green banking disclosure. Independent commissioners do not significantly affect green banking disclosure, and the audit committee's findings indicate a weak statistical relationship between the two variables Research limitations/Implications – The observation period is relatively short, only three years, which limits the ability to assess the development of green banking disclosure practices more comprehensively. Keywords:  Corporate Governance, Disclosure, Green Banking, Indonesia, Ownership Structure